The clinical pharmacist in the private community pharmacy: integrative review (Research, Society and Development, 2021)
The implementation of clinical pharmaceutical services was initiated in a hospital environment and later expanded to private community pharmacies. The aim of the article is to carry out a synthesis of evidence on the importance of the clinical pharmacist in the private community pharmacy, providing users with efficient treatments and improving the quality of life. Method: This is an integrative review based on bibliographical research, a method that groups the relevant scientific production on a pre-established topic. Results and discussion: 14 articles were selected, being 08 of them literature reviews, 01 cross-sectional study, 01 systematic review with narrative synthesis and 04 integrative bibliographic studies, one of which was a quantitative study. The studies contemplate and synthesize the importance of the clinical pharmacist in private community pharmacy. Conclusion: The evidence presented in this study demonstrates the action of the clinical pharmacist in community pharmacy, demonstrating that this professional is responsible for handling, dispensing and providing guidance on the use of medications.